2015
DOI: 10.1016/j.endm.2015.06.071
|View full text |Cite
|
Sign up to set email alerts
|

Local resilience of spanning subgraphs in sparse random graphs

Abstract: For each real γ > 0 and integers ∆ ≥ 2 and k ≥ 1, we prove that there exist constants β > 0 and C > 0 such that for all p ≥ C(log n/n) 1/∆ the random graph G(n, p) asymptotically almost surely contains -even after an adversary deletes an arbitrary (1/k − γ)-fraction of the edges at every vertex -a copy of every nvertex graph with maximum degree at most ∆, bandwidth at most βn and at least C max{p −2 , p −1 log n} vertices not in triangles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…is a threshold for the existence of a K Δ+1 -factor. It is believed that K Δ+1 -factors are graphs which are most "difficult" to embed, meaning that for any other graph H ∈ (n, Δ) the bound on p given in (1) suffices. This belief is supported by a result of Riordan [30] which shows that p ≥ n −2∕(Δ+1)+ (Δ) suffices, for some (Δ) > 0 which goes to 0 as Δ goes to infinity, and a recent result of Ferber, Luh and Nguyen [15] where they showed that this is indeed the case if H has at most (1 − )n vertices (we call such graphs almost-spanning).…”
Section: δ+1mentioning
confidence: 99%
See 2 more Smart Citations
“…is a threshold for the existence of a K Δ+1 -factor. It is believed that K Δ+1 -factors are graphs which are most "difficult" to embed, meaning that for any other graph H ∈ (n, Δ) the bound on p given in (1) suffices. This belief is supported by a result of Riordan [30] which shows that p ≥ n −2∕(Δ+1)+ (Δ) suffices, for some (Δ) > 0 which goes to 0 as Δ goes to infinity, and a recent result of Ferber, Luh and Nguyen [15] where they showed that this is indeed the case if H has at most (1 − )n vertices (we call such graphs almost-spanning).…”
Section: δ+1mentioning
confidence: 99%
“…This belief is supported by a result of Riordan [30] which shows that p ≥ n −2∕(Δ+1)+ (Δ) suffices, for some (Δ) > 0 which goes to 0 as Δ goes to infinity, and a recent result of Ferber, Luh and Nguyen [15] where they showed that this is indeed the case if H has at most (1 − )n vertices (we call such graphs almost-spanning). Moreover, it is also believed that for p being of order what is given in (1), not only that G n,p contains one such graph H ∈ (n, Δ) almost surely but it contains every graph from (n, Δ) simultaneously. In other words, a typical G n,p is (n, Δ)-universal.…”
Section: δ+1mentioning
confidence: 99%
See 1 more Smart Citation
“…For local resilience, the best previously known results are by Noever and Steger and Allen, Böttcher, Ehrenmüller, and Taraz , for the square of a cycle and higher powers, respectively. The former states that for any ε , γ > 0, if p ≥ N −1/2 + γ the local resilience of GN , p with respect to having the square of a cycle on (1 − ε ) N vertices is 1/3 + o (1), while the latter is a variant of the bandwidth theorem for sparse random graphs and implies that for any k ≥ 2, if p ≫ N −1/(2 k ) the local resilience of GN , p with respect to containing a k ‐cycle on all but O ( p −2 ) vertices, is 1/( k + 1) + o (1).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the “leftover” given by Theorem is εN , which for k = 2 and the conjectured appearance threshold p ≥ N −1/2 would correspond to the optimal O ( p −2 ). However, as our bound on p is slightly larger, this leaves a small gap with respect to the result of Allen et al .…”
Section: Introductionmentioning
confidence: 99%